Suramin action in African trypanosomes involves a RuvB-like DNA helicase - Anna Albisetti; Silvan Hälg; Martin Zoltner; Pascal Mäser; Natalie Wiedemar (International Journal for Parasitology: Drugs and Drug Resistance, 2023)
Suramin is one of the oldest drugs in use today. It is still the treatment of choice for the hemolymphatic stage of African sleeping sickness caused by Trypanosoma brucei rhodesiense, and it is also used for surra in camels caused by Trypanosoma evansi. Yet despite one hundred years of use, suramin's mode of action is not fully understood. Suramin is a polypharmacological molecule that inhibits diverse proteins. Here we demonstrate that a DNA helicase of the pontin/ruvB-like 1 family, termed T. brucei RuvBL1, is involved in suramin resistance in African trypanosomes. Bloodstream-form T. b. rhodesiense under long-term selection for suramin resistance acquired a homozygous point mutation, isoleucine-312 to valine, close to the ATP binding site of T. brucei RuvBL1. The introduction of this missense mutation, by reverse genetics, into drug-sensitive trypanosomes significantly decreased their sensitivity to suramin. Intriguingly, the corresponding residue of T. evansi RuvBL1 was found mutated in a suramin-resistant field isolate, in that case to a leucine. RuvBL1 (Tb927.4.1270) is predicted to build a heterohexameric complex with RuvBL2 (Tb927.4.2000). RNAi-mediated silencing of gene expression of either T. brucei RuvBL1 or RuvBL2 caused cell death within 72 h. At 36 h after induction of RNAi, bloodstream-form trypanosomes exhibited a cytokinesis defect resulting in the accumulation of cells with two nuclei and two or more kinetoplasts. Taken together, these data indicate that RuvBL1 DNA helicase is involved in suramin action in African trypanosomes.